1989
DOI: 10.1523/jneurosci.09-10-03513.1989
|View full text |Cite
|
Sign up to set email alerts
|

Restraint-stress-induced changes in exploratory behavior appear to be mediated by norepinephrine-stimulated release of CRF

Abstract: Exploratory behavior, measured by the time an animal spends investigating objects in a novel environment, has been shown to be sensitive to prior exposure of the animal to stressors. or the number of rears. These results implicate noradrenergic systems in the stress-related changes in this behavior, consistent with our parallel measures of the production of NE catabolites. Thus, both CRF and noradrenergic systems appear to be involved in the effect of restraint on exploratory behavior in this task. Neither DSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(48 citation statements)
references
References 48 publications
3
44
1
Order By: Relevance
“…Likewise, it has been demonstrated that female Fischer rats are more sensitive to CRH-induced ACTH augmentation than Lewis rats (Spinedi et al, 1994). These findings, taken together with the strain differences we observed in both CRH and corticosterone availability at the anterior pituitary gland, suggest that at least one of the underlying mechanisms mediating the strain differences may be related to the apparent strain-dependent sensitivity to the effects of CRH, which would then impact stressor-associated HPA activation and behavioral change (Berridge and Dunn, 1989).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Likewise, it has been demonstrated that female Fischer rats are more sensitive to CRH-induced ACTH augmentation than Lewis rats (Spinedi et al, 1994). These findings, taken together with the strain differences we observed in both CRH and corticosterone availability at the anterior pituitary gland, suggest that at least one of the underlying mechanisms mediating the strain differences may be related to the apparent strain-dependent sensitivity to the effects of CRH, which would then impact stressor-associated HPA activation and behavioral change (Berridge and Dunn, 1989).…”
Section: Discussionsupporting
confidence: 66%
“…Our results also make it tempting to suggest that noise exposure might have protracted effects on CRH changes related to the exposure environment and that Lewis rats might be more sensitive to these cues compared to Fischer rats. Such findings, along with those that suggest that stressors might sensitize processes associated with neurotransmitter release (Berridge and Dunn, 1989;Zhang et al, 1995) or alter co-expression of neuropeptides within hypothalamic neurons (Bartanusz et al, 1993;Schmidt et al, 1996), indicate that aversive events, such as environmental noise exposure, may have long-term repercussions that could impact on behavioral outputs. However, it is likely that the impact of such events may be dependent on individual characteristics, including genetic disposition.…”
Section: Discussionmentioning
confidence: 84%
“…When tissue levels of monoamines are measured in KO mice at a time of stereotypic activation, 5-HT metabolism is increased in all three brain regions. By contrast, in WT animals, OF exposure alters DA levels in frontal cortex and 5-HIAA is increased only in frontal cortex and caudate putamen which may reflect stress of the test conditions (Berridge and Dunn, 1989;Ge et al, 1997). Hence, in KO mice interactions between dopaminergic and serotonergic neurotransmission are perturbed.…”
Section: Discussionmentioning
confidence: 91%
“…Previous studies have shown that ICV infusions of this compound blocked the effect of acute stress on various behavioral measures at doses ranging from 5 to 50 ÎŒg (Krahn et al, 1986;Kalin et al, 1988;Berridge and Dunn, 1989;Cole et al, 1990;Nawata et al, 2012). In the present study, we infused 30 ÎŒg/4 ÎŒl, dissolved in distilled water.…”
Section: Drugs and Microinfusion Proceduresmentioning
confidence: 85%